(3JaSjQ GdJHQjRis - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s ((3SYjO Hf GdTgGH s)
(3ChdgG (B:s
(3Yf CHj YHGS fRdJ ShQI GdCfYGe MjdI djdkG hMhdgG SHYhf edckG s
(3BNQgG (B:s
(3ef Ghd ShQI GHQGgje Edi GdeNdO CHh GdYHGS s
(3hgh edc GdabjQ YHOGddg GHQGgje GdLYjQis
(3hgh ef Chd ShQI GdCfYGe Edi BNQ ShQI GdeDefjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B214 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B519s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B446 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B123s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs